Renaissance Utopias and the Problem of History - Leslie, Marina (Cornell University Press, 2019)
Marina Leslie draws on three important early modern utopian texts-Thomas More's Utopia, Francis Bacon's New Atlantis, and Margaret Cavendish's Description of a New World Called the Blazing World-as a means of exploring models for historical transformation and of addressing the relationship of literature and history in contemporary critical practice. While the genre of utopian texts is a fertile terrain for historicist readings, Leslie demonstrates that utopia provides unstable ground for charting out the relation of literary text to historical context. In particular, she examines the ways that both Marxist and new historicist critics have taken the literary utopia not simply as one form among many available for reading historically but as a privileged form or methodological paradigm. Rather than approach utopia by mapping out a fixed set of formal features, or by tracing the development of the genre, Leslie elaborates a history of utopia as critical practice. Moreover, by taking every reading of utopia to be as historically symptomatic as the literary production it assesses, her book integrates readings of these three English Renaissance utopias with an analysis of the history and politics of reading utopia. Throughout, Leslie considers utopia as a fictional enactment of historical process and method. In her view, these early modern utopian constructions of history relate very closely to and impinge upon the narrative structures of history assumed by critical theory today.